Diameter, pressure and compliance relationships in dorsal hand veins - Shykoff, Barbara E; Hawari, Feras I; Izzo, Joseph L (Vascular medicine (London, England), 2001)
The diameter-pressure characteristics of dorsal hand veins previously have not been characterized. In this study, the effects of distending pressure with and without infused norepinephrine on diameter and compliance were observed. The elevation needed for venous collapse was measured, and the effects of baseline constriction on venous reactivity were assessed. In seven supine subjects, a brachial cuff on an elevated arm was used to generate distending pressures while a linear variable displacement transformer (LVDT) measured changes in venous diameter. Arctangent functions of distending pressure were fitted to the normalized diameter, then compliance functions were calculated. In supine subjects, 5-15 cm of elevation emptied dorsal hand veins. Norepinephrine decreased the venous diameter at any distending pressure by increasing the P 50 without significantly changing the midpoint slope. Compliance was a nearly single-valued function of the normalized diameter with a maximum value at about 60% distention. Reactivity depends on distending pressure and baseline P 50. Percentage constriction is a function of initial and final P 50 and of distending pressure.